Development of biogranules using selected mix culture of decolourising bacteria for treatment of textile wastewater - Kee, Thuan Chien (2012)
Biological treatment of textile wastewater using granules involves the application of self-immobilisation of high density biomass under intermittent facultative anaerobic and aerobic system. Since granules are dense and have high settling velocity, high density of active biomass to be retained without being washed out, minimising previous problems of using suspended biomass in treating textile wastewater. The use of synthetic wastewater containing single or several combinations of dyes for the development of granules has been widely studied. However, little has been reported on the development of granules using more complex and toxic real textile wastewater. Hence, there is a need to develop granules that are well adapted to real textile wastewater in order to improve the treatment efficiency. In this study, granules consisting of bio-augmented consortium of four locally isolated decolourising bacteria were successfully developed under intermittent facultative anaerobic-aerobic system. Sludge was added as seeding agent in a single 1 L SBR reactor at hydraulic retention time (HRT) of 6 h. The 16S rDNA molecular analysis showed that ZK1 (JQ773350), ZK2 (JQ773351), ZB1 (JF742762) and ZB2 (JF742761) were closely related to Bacillus pumilus, Bacillus cereus, Brevibacillus panacihumi and Lysinibacillus fusiformis respectively. After 112 days, the size of the granules reached 3.3 ± 1 mm and were dark grey in colour, with integrity coefficient of 25 ± 2, settling velocity of 56 ± 5 m h-1 and sludge volume index (SVI) of 35 ± 5.5 mL g-1. Biomass concentration was 13 ± 0.8 g L-1 and 11 ± 0.6 g L-1 for MLSS and MLVSS respectively. In general, the developed granules showed good removal for colour (70 %; initial ADMI values ranging from 500 to 2000) and COD (53 %; initial values ranging from 400 to 1,500 mg L-1) at HRT of 24 h with intermittent facultative anaerobic (18 h) and aerobic (6 h).